2013
DOI: 10.1002/mmce.20727
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of resolution limits for indirect microwave holographic imaging

Abstract: This work describes how indirect holography which has previously been applied to the determination of antenna radiation patterns can be adapted for the imaging of passive objects. It provides details of how complex scattered field values can be obtained in a simple and inexpensive manner from sampled scalar intensity measurements taken over a single scanning aperture. This work uses indirect holographic techniques to image a number of simple objects including a rectangular metallic plate, a small metal plate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…For applications where linear phase shift and sample spacing selections do not provide enough separation between the PWS components to achieve a proper component filtering due to an overlap, two solutions can be applied. One way to overcome this challenge is to decrease the sample spacing to increase the offset wave vector kr as given in (5) which would also result in an increase in the number of the sampling points required for the imaging. Therefore, this solution would increase the required total measurement and computational time.…”
Section: A Indirect Microwave Holographic Twi Of a Concealed Gunmentioning
confidence: 99%
See 1 more Smart Citation
“…For applications where linear phase shift and sample spacing selections do not provide enough separation between the PWS components to achieve a proper component filtering due to an overlap, two solutions can be applied. One way to overcome this challenge is to decrease the sample spacing to increase the offset wave vector kr as given in (5) which would also result in an increase in the number of the sampling points required for the imaging. Therefore, this solution would increase the required total measurement and computational time.…”
Section: A Indirect Microwave Holographic Twi Of a Concealed Gunmentioning
confidence: 99%
“…Previous work on the use of indirect microwave holography was successfully demonstrated for the measurement of complex antenna near-field and far-field radiation patterns [2][3][4]. Recently, this technique has been extended to the inverse scattering problem and the imaging of metallic objects has successfully been demonstrated [5][6][7][8]. Indirect microwave holography differs from conventional microwave imaging techniques in that it does not require the direct measurement of the complex field but "indirectly" recovers it from intensity-only measurements performed using a low-cost scalar microwave power meter.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was originally developed for determining the complex aperture fields of antennas without using vector measurement equipment [20] and subsequently extended for imaging of metallic objects [21]. For the detection of metal objects, it was shown that the image can be reconstructed from amplitude measurements taken with a low-cost power meter.…”
Section: Indirect Microwave Holographymentioning
confidence: 99%
“…In the literature, indirect microwave holography was proved to have a significant potential to be employed in the measurement of complex antenna near-field and far-field radiation patterns [12,13]. Recently, this technique has been extended to the imaging of early-stage breast cancer tumors [14] and unconcealed metallic objects [15]. Although promising results have been achieved in [14,15], the reconstruction of the original scattered field in these works was limited to the measurement plane.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this technique has been extended to the imaging of early-stage breast cancer tumors [14] and unconcealed metallic objects [15]. Although promising results have been achieved in [14,15], the reconstruction of the original scattered field in these works was limited to the measurement plane. This brings a significant challenge for the imaging of concealed objects, which requires the reconstruction of the scattered field at the object plane under the concealed medium to achieve optimum imaging response.…”
Section: Introductionmentioning
confidence: 99%